2012
DOI: 10.1093/arclin/acs049
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Socio-Demographic Characteristics on DRS-2 Performance in Spanish-Speaking Older Adults

Abstract: The present study compared the performance of English- and Spanish-speaking healthy controls (HCs) on the Spanish translation of the Dementia Rating Scale-Second edition (ST-DRS-2) and examined the classification accuracy of the ST-DRS-2 and Mini-Mental State Examination (MMSE) with an age- and education-matched clinical sample. In contrast to previous findings with English-speakers, a stronger relationship was observed between ST-DRS-2 Total scores and education than with age, and despite being matched on bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 16 publications
0
13
0
1
Order By: Relevance
“…As aforementioned, the results of this study confirm the influence of education level on the performance on DRS. 3,[8][9][10]20,21 Regarding the subtests, this influence was stronger on the CONCEPT subscale and moderate on the I/P and ATT subscales.…”
Section: Discussionmentioning
confidence: 94%
“…As aforementioned, the results of this study confirm the influence of education level on the performance on DRS. 3,[8][9][10]20,21 Regarding the subtests, this influence was stronger on the CONCEPT subscale and moderate on the I/P and ATT subscales.…”
Section: Discussionmentioning
confidence: 94%
“…Our findings showed that being male, older and obtaining lower WAT scores were associated with poor performance on the MDRS‐2. The influence of age and education on MDRS‐2 scores has been widely demonstrated in the literature (Rilling et al ., ; Katsarou et al ., ; Strutt et al ., ; Lavoie et al ., ). We found a strong influence of gender on the global scale and the IP subscale, with women scoring higher than men.…”
Section: Discussionmentioning
confidence: 99%
“…() provided age‐ and education‐corrected norms of MDRS derived from a sample of 623 community‐dwelling Caucasian over 55 years old. Like with most neuropsychological instruments, younger and better educated individuals obtain higher results on the MDRS (Bank et al ., ; Rilling et al ., ; Strutt et al ., ); however, the effect of gender has been controversial (Chan et al ., ; Lyness et al , ; Pedraza et al ., ; Lavoie et al ., ). Moreover, it should be noted that reading level is a stronger predictor of cognitive performance than years of education among Spanish‐speaking individuals (Contador et al ., ), and cognitive function is influenced by socioeconomic status across the lifecourse (Turrell et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, several authors have documented the significant association between age and DRS score, with younger subjects performing better than older ones (e.g., Baird, 2006;Bank, Yochim, MacNeill & Lichtenberg, 2000;Pedraza et al, 2010;Rilling et al, 2005;Strutt et al, 2012). A positive correlation between education level and performance on the DRS was also consistently reported (e.g., Bank et al, 2000;Lyness, Hernandez, Chui & Teng, 2006;Pedraza et al, 2010;Rilling et al, 2005;Strutt et al, 2012). The effect of gender, however, is less clear.…”
mentioning
confidence: 98%
“…Indeed, although the two groups were matched for years of education, their educational experience was not necessarily comparable. Recently, Strutt et al (2012) found that American English-speaking subjects out-performed age-and education-matched American Spanish-speaking subjects assessed with a Spanish translation of the DRS-2. The greatest difference between the two groups was found on the Memory subscale, where most errors of Spanish-speaking participants were committed on three specific orientation items: current president, governor and mayor, items significantly related to their level of acculturation.…”
mentioning
confidence: 99%